Pengaruh Gaya Kepemimpinan, Budaya Organisasi, dan Disiplin Kerja Terhadap Kinerja Pegawai Pada Sekretariat Daerah Kabupaten Pesawaran - Yori Tirta Kusuma (Jurnal Administrativa, 2023)
Performance can be known and measured if a group of people or individuals have achieved the criteria or standards of success that have been set by the organization. However, not all human resources in an organization are quality as expected by the organization. There are several factors that can affect the performance of an organization including, the decreased desire of employees to achieve work performance, lack of punctuality in completing work, the influence of the environment or organizational culture. Therefore, it is very important to utilize organizational resources. Based on this, the researcher intends to determine the effect of leadership style, organizational culture, and work discipline on employee performance at Sekretariat Daerah Kabupaten Pesawaran. The sample of this study amounted to 167 people. The sampling technique used was probability sampling with a sample random sampling method. Collecting data using questionnaire. The data analysis technique is multiple regression analysis. Based on the results of multiple regression analysis, it can be seen that leadership style, organizational culture, and work discipline have a positive and significant effect on the performance of the employees at Sekretariat Daerah Kabupaten Pesawaran.